Anti Neutrosophic multi fuzzy ideals of near ring - K. Hemabala; B. Srinivasa Kumar (Neutrosophic Sets and Systems, 2022)
The theory of anti neutrosophic multi fuzzy ideals of y near ring is dispensed in this work and various algebraic properties such as intersection, union of anti neutrosophic multi fuzzy ideals of y near ring are examined. Further we examined the direct anti product of anti neutrsophic multi fuzzy ideals of y near ring and also we proved the homorphic images and pre images of anti neutrosophic multi fuzy ideals of y near ring